O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

A perspectiva de género no desenho dos programas de protecção social em Moçambique: o caso do programa Acção Social Produtiva - Chiboleca, Gil Tomás; Cremades, Raquel Coello (Faculdade Latino Americana de Ciências Sociais, 2015)
Este trabalho aborda uma das questões centrais no debate sobre a protecção social: género no desenho dos programas de protecção social. Neste contexto, o presente estudo analisa a integração da perspectiva de género no desenho dos programas de protecção social em Moçambique, tomando como estudo de caso – o Programa Acção Social Produtiva. Para a materialização deste trabalho, a nossa proposta de percurso metodológico, em conformidade com os objectivos propostos, o nosso quadro analítico irá guiar-se pelas variáveis centrais: (i) Objectivos gerais e específicos do programa; e (ii) Grupo-alvo (Beneficiários do programa). O estudo constatou que a integração da perspectiva de género nos programas de protecção social é complexa, limitada, e varia de acordo com as características e objectivos de cada programa de protecção social. Ademais, em alguns casos, a consideração de género nos programas é feita através da inclusão das mulheres como principais beneficiárias, ignorando a dimensão do género no seu todo. Na análise do PASP na óptica de género, o trabalho conclui que o programa não incorpora de forma explícita a perspectiva de género, e que a promoção da igualdade de género não constitui um objectivo primário na concepção do PASP. A análise dos grupos-alvo mostra que a consideração de género no PASP é feita através da inclusão da mulher como grupo-alvo prioritário. Isto acontece, como defende o presente estudo, pelo facto do PASP não ter sido desenhado/concebido com o intuito de promover a igualdade de género e empoderamento da mulher, mas para proteger os grupos vulneráveis aliviando a pobreza, e preveni-los contra a indigência e a fome.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; social protection / proteção social

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude